Anonymous DoS-Resistant Access Control Protocol using Passwords for Wireless Networks - WAN, Zhiguo (Institutional Knowledge at Singapore Management University, 2005)
Wireless networks have gained overwhelming popularity over their wired counterpart due to their great flexibility and convenience, but access control of wireless networks has been a serious problem because of the open medium. Passwords remain the most popular way for access control as well as authentication and key exchange. But existing password-based access control protocols are not satisfactory in that they do not provide DoS-resistance or anonymity. In this paper we analyze the weaknesses of an access control protocol using passwords for wireless networks in IEEE LCN 2001, and propose a different access control protocol using passwords for wireless networks. Our new protocol avoids the weaknesses of the previous protocol, and the client can anonymously authenticate himself to the server with a human-memorable password, while the server is free of DoS attacks. We also present detailed security and performance analysis for our protocols, and show that our protocol is both secure and efficient for access control in wireless networks